A review on using an alcohol-based sanitizer as a prophylactic measure against microorganisms - Ranabhat, Priyanka; Khatiwara, Deepika; Paul, Moumita; Bagchi, Arnab (Creative Pharma Assent, 2021)
Because of the COVID 19 pandemic, we now utilise hand sanitizer in our daily lives. Hand hygiene has become a legal requirement. Infection control is becoming a requirement. Hand hygiene is widely regarded as the most practical and effective way of infection prevention. Hand sanitizer is thought to have played a significant role in reducing illness transmission to patients. Because it is more cost-effective and efficient. The efficiency of hand sanitizer is totally determined by how it is used. There are two sorts of hand sanitizers on the market. 1) Hand sanitizer with alcohol 2) Hand sanitizer that isn't alcohol-based. Most effective hand sanitizers contain 70 percent to 95 percent alcohol, which has the potential to denature microbial protein and inactivate viruses. The impact of hand sanitizer on human health care is significant, and this review article will provide you with information on several elements of hand sanitizer